Social Media Utilization by Preachers to Shape Religious Perceptions among Indonesian Youth - Rokibullah, Rokibullah; Laksana, Medika Oga (Islamic Journal of Communication and Public Discourse, 2025)
The development of digital technology has changed the way religious teachings are disseminated, with social media becoming the main channel for preaching to the younger generation. This phenomenon illustrates the transformation of religious authority from physical to virtual spaces, shaping the way Indonesian youth understand and internalize religious values. This study aims to analyze how digital da'wah communication strategies shape religious perceptions among Indonesian youth. Using a qualitative approach with a case study method, this study examined 150 da'wah contents from five popular preachers on YouTube, Instagram, and TikTok. The data were analyzed using NVivo 14 software, which helped identify da'wah themes, communication styles, and audience responses. The results show that the personal storytelling approach and creative visualization are the main strategies in shaping religious perceptions that are more personal and contextual. Most of the content focuses on the themes of morals and worship, although intolerance-themed content still has high emotional appeal. This research confirms the importance of faith-based digital literacy to strengthen youth resilience against extreme religious content. The implications of this research underscore the need for collaboration between religious institutions, academics, and digital platforms in building a moderate and inclusive da'wah ecosystem in the social media era.